Strategi Peningkatan Profesionalitas Guru Pada Mgmp Bahasa Inggris(Studi Kasus Pokja 5 Smp Karanganyar) - Darmanto, Priyono Eko Setyo, Dr. Eko Supriyanto, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
This study aims to: (1) describe the role of the deliberations of subject teachers in improving the professionalism of teachers in the deliberations of subject teachers of junior high school English working group 5 Karanganyar; (2) know the model increase the professionalism of teachers in the deliberations of subject teachers of junior high school English working group 5 Karanganyar; (3) know the effectiveness of the development strategy of the professionalism in the deliberations of subject teachers of junior high school English working group 5 Karanganyar. This research was conducted using qualitative approach. The strategy used is the phenomenological study. This study was conducted in the deliberations of subject teachers of junior high school English working group 5 Karanganyar. Sources of data obtained from informants that management and members in the deliberations of subject teachers of junior high school English working group 5 Karanganyar by in-depth interviews, observation and record documents. Technique analysis of data is by data reduction, data display and conclusion drawing or verification. To obtain data validity researcher used data triangulation method, continuous observation and interview. Results of this study found some important points that relate to the focus of research, among others: (1) Implementation of the program in the deliberation subject teachers English SMP working group 5 Karanganyar is by planning, implementing and evaluating program; (2) Strategy in improving the professionalism of teachers in the deliberation subject teachers English SMP working group 5 Karanganyar is by training, non training, certification program and educating supervise program; (3) The development model of the professionalism of English teachers is effective to improve the professionalism of English teachers by four domains, namely: the realm of the needs of teachers analysis, sphere of activity in the MGMP, the realm of evaluation and feedback, and the realm of the increase in the professionalism of teachers. This model emphasizes the importance of evaluation and feedback on program implementation of deliberation subject teachers.